Molecular characterization and antioxidant activity of Volkameria inermis L. - Thiripura Sundari, U.; Shanthi, P. (Current Botany, 2022)
The present investigation aimed to study the genomic characterization and free radical scavenging potential of a traditional plant Volkameria inermis. A chloroplast genome rbcL was used in molecular characterization and it revealed the phylogeny and evolutionary affinities of V. inermis with the outgroups of the family through BLAST search based on Neighbor-Joining (NJ) analysis. The free radical scavenging potential of various extracts of V. inermis was observed at different concentrations (20, 40, 60, 80 and 100 μg/mL) in DPPH and ABTS in vitro models. Ascorbic acid (DPPH) and Trolox (ABTS) were used as standard. In DPPH assay, among the different extracts (hexane, chloroform, acetone, ethanol, methanol and water) tested, methanol showed maximum scavenging activity with the IC50 value of 28.33μg/mL followed by acetone with the IC50 value of 31.937μg/mL. The other extracts, ethanol and water extracts showed moderate activity with the IC 50 value of 82.558 μg/mL and 81.758μg/mL; chloroform and hexane showed very lower antioxidant activity and the IC50 values are 518.776μg/mL, 1066.16μg/mL accordingly. In ABTS assay, methanol was observed as a highly active extracts with the IC50 value of 70.196μg/mL followed by ethanol extract (103.078μg/mL). The results showed that the methanol extract exhibits strong antioxidant activity in DPPH and ABTS assays. The scavenging efficiency showed dose dependent increase in concentration absorption compared to Ascorbic acid and Trolox. Our findings provide the molecular identification and evidence for the potential of Volkameria inermis as a source of natural antioxidants.